Optimizing the role of Puskesos-SLRT facilitators through capacity building training - Maulana Maulana; Encep Sudirjo; Dadan Nugraha; Enjang Yusup Ali; Heri Ridwan (Jurnal Abmas, 2026)
The Social Welfare Center-Integrated Service and Referral System (Puskesos-SLRT) is a community-based institution designed to improve access to social welfare services for poor and vulnerable populations at the village and sub-district levels. In practice, the implementation of Puskesos-SLRT services has encountered major challenges, particularly the limited capacity of facilitators in managerial skills, social service delivery, and social data management. Therefore, this community service program aimed to enhance the capacity of Puskesos-SLRT facilitators in Sumedang Regency to enable them to perform their roles more effectively. The program was implemented through structured training, continuous mentoring, and capacity-building activities involving facilitators from 277 villages and sub-districts. The evaluation of capacity improvement was conducted using a descriptive qualitative approach through observation, reflective discussions, and assessments of facilitators’ understanding of their roles and service functions before and after the program. The results indicate an improvement in facilitators’ understanding of social welfare service management, increased responsiveness to community needs, and strengthened coordination with local government institutions. Overall, this community service activity contributed to optimizing the role of Puskesos-SLRT facilitators in delivering more effective and integrated social welfare services at the local level   Abstrak Pusat Kesejahteraan Sosial-Sistem Layanan dan Rujukan Terpadu (Puskesos-SLRT) merupakan lembaga berbasis masyarakat yang berperan dalam mendekatkan layanan kesejahteraan sosial bagi masyarakat miskin dan rentan di tingkat desa dan kelurahan. Dalam praktiknya, pelaksanaan layanan Puskesos-SLRT masih menghadapi kendala utama berupa keterbatasan kapasitas sumber daya manusia fasilitator, khususnya pada aspek manajerial, keterampilan pelayanan sosial, dan pengelolaan data. Oleh karena itu, kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas fasilitator Puskesos-SLRT di Kabupaten Sumedang agar mampu menjalankan perannya secara lebih optimal. Pengabdian dilaksanakan melalui pelatihan terstruktur, pendampingan, dan pembinaan berkelanjutan yang melibatkan fasilitator dari 277 desa dan kelurahan. Metode evaluasi peningkatan kapasitas fasilitator dilakukan secara deskriptif kualitatif melalui observasi, diskusi reflektif, serta evaluasi pemahaman terhadap tugas dan fungsi layanan sebelum dan setelah kegiatan. Hasil pengabdian menunjukkan adanya peningkatan pemahaman fasilitator terhadap manajemen layanan kesejahteraan sosial, meningkatnya responsivitas dalam menangani kebutuhan masyarakat, serta penguatan koordinasi dengan perangkat pemerintah daerah. Secara keseluruhan, kegiatan ini berkontribusi pada optimalisasi peran fasilitator Puskesos-SLRT dalam penyelenggaraan layanan kesejahteraan sosial yang lebih efektif dan terpadu di tingkat lokal. Kata Kunci: fasilitator; peningkatan kapasitas SDM; pusat kesejahteraan sosial